Chemical Tuning of Specific Capacitance in Functionalized Fluorographene - Vermisoglou, Eleni C; Jakubec, Petr; Bakandritsos, Aristides; Pykal, Martin; Talande, Smita; Kupka, Vojtěch; Zbořil, Radek; Otyepka, Michal (Chemistry of materials, 2019)
Owing to its high surface area and excellent conductivity, graphene is considered an efficient electrode material for supercapacitors. However, its restacking in electrolytes hampers its broader utilization in this field. Covalent graphene functionalization is a promising strategy for providing more efficient electrode materials. The chemistry of fluorographene is particularly attractive as it allows scalable chemical production of useful graphene derivatives. Nevertheless, the influence of chemical composition on the capacitance of graphene derivatives is a largely unexplored field in nanomaterials science, limiting further development of efficient graphene-based electrode materials. In the present study, we obtained well-defined graphene derivatives differing in chemical composition but with similar morphologies by controlling the reaction time of 5-aminoisophthalic acid with fluorographene. The gravimetric specific capacitance ranged from 271 to 391 F g-1 (in 1 M Na2SO4), with the maximum value achieved by a delicate balance between the amount of covalently grafted functional groups and density of the sp2 carbon network governing the conductivity of the material. Molecular dynamics simulations showed that covalent grafting of functional groups with charged and ionophilic/hydrophilic character significantly enhanced the ionic concentration and hydration due to favorable electrostatic interactions among the charged centers and ions/water molecules. Therefore, conductive and hydrophilic graphitic surfaces are important features of graphene-based supercapacitor electrode materials. These findings provide important insights into the role of chemical composition on capacitance and pave the way toward designing more efficient graphene-based supercapacitor electrode materials.